2020
DOI: 10.1101/2020.08.31.275834
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attenuation of homeostatic signaling from apoptotic thymocytes triggers a global regenerative response in the thymus

Abstract: The molecular triggers of organotypic tissue repair are unknown. The thymus, which is the primary site of T cell development, is a model of tissue damage and regeneration as it is particularly sensitive to insult, but also has a remarkable capacity for repair. However, acute and profound damage, such as that caused by common cytoreductive therapies or age-related decline, lead to involution of the thymus and prolonged T cell deficiency, precipitating life-threatening infections and malignant relapse. Consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…To determine if there was a direct effect of Zn on thymic ECs, we constitutively activated the Akt pathway using the prosurvival adenoviral gene E4ORF1, which allows ECs from multiple tissues, including the thymus, to be propagated and manipulated ex vivo while maintaining their phenotype and vascular tube formation for functional manipulation and in vitro modeling of regenerative pathways 27,39,40 . Using this approach, we found that ECs showed a dose-dependent increase in the transcription of Bmp4 by qPCR after 24 hours of exposure to exogenous Zn (Fig.…”
Section: Zinc Stimulates the Production Of Bmp4 By Thymic Endothelial Cellsmentioning
confidence: 99%
“…To determine if there was a direct effect of Zn on thymic ECs, we constitutively activated the Akt pathway using the prosurvival adenoviral gene E4ORF1, which allows ECs from multiple tissues, including the thymus, to be propagated and manipulated ex vivo while maintaining their phenotype and vascular tube formation for functional manipulation and in vitro modeling of regenerative pathways 27,39,40 . Using this approach, we found that ECs showed a dose-dependent increase in the transcription of Bmp4 by qPCR after 24 hours of exposure to exogenous Zn (Fig.…”
Section: Zinc Stimulates the Production Of Bmp4 By Thymic Endothelial Cellsmentioning
confidence: 99%